2022
DOI: 10.3389/fnhum.2022.1009219
|View full text |Cite
|
Sign up to set email alerts
|

Systematic errors in the perception of rhythm

Abstract: One hypothesis for why humans enjoy musical rhythms relates to their prediction of when each beat should occur. The ability to predict the timing of an event is important from an evolutionary perspective. Therefore, our brains have evolved internal mechanisms for processing the progression of time. However, due to inherent noise in neural signals, this prediction is not always accurate. Theoretical considerations of optimal estimates suggest the occurrence of certain systematic errors made by the brain when es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…It would be possible that more than three bursts elicit stronger MOCR because an increase of the number of preceding tone bursts may improve the accuracy of the prediction on the timing of the MOCR elicitor arrival. Mansuri et al (2022) reported that accuracy of rhythm perception was higher as the number of beats increased [ 44 ]. Considering that Mansuri et al (2022) varied the number of beats form 3 to 8, it is reasonable to suppose that more preceding tone bursts would drive larger enhancement of MOCR, although the number of preceding tone bursts in the present study was limited to less than three.…”
Section: Discussionmentioning
confidence: 99%
“…It would be possible that more than three bursts elicit stronger MOCR because an increase of the number of preceding tone bursts may improve the accuracy of the prediction on the timing of the MOCR elicitor arrival. Mansuri et al (2022) reported that accuracy of rhythm perception was higher as the number of beats increased [ 44 ]. Considering that Mansuri et al (2022) varied the number of beats form 3 to 8, it is reasonable to suppose that more preceding tone bursts would drive larger enhancement of MOCR, although the number of preceding tone bursts in the present study was limited to less than three.…”
Section: Discussionmentioning
confidence: 99%